Analisa Penyebab Dan Penanganan Titik Lokasi Blackspot Jalan Nasional Ruas Tobali – Poso Provinsi Sulawesi Tengah - Asril, Muhammad; Nurdin, Abdul Rahim; Mallawangeng , Tamrin (Program Studi Teknik Sipil Universitas Bosowa, 2024)
Blackspots are locations on a road network that have a frequency of accidents or the number of traffic accidents per year that is greater than the specified minimum number of 30. With the effectiveness of efforts to handle accident-prone areas or Blackspots, it is hoped that accident cases will continue to decline from year to year and minimize the risk. Blackspots. The research was carried out on the Toboli - Poso section, Central Sulawesi Province, with the aim of determining the factors that cause Blackspots and how to alternatively handle Blackspots on this section. The research method used is a survey. The results obtained show that the causes of Blackspots are driver negligence in driving, vehicle factors, and the lack of adequate infrastructure on road sections that are prone to accidents, as well as road elements that are still not good and/complete. This triggers accidents that can result in fatalities such as serious injuries. Peak time for accidents often occurs at 12.00 - 18.00 WITA, the types of collisions are motor vehicles and pedestrians. Handling that can be carried out in Blackspot areas is by controlling traffic speeds, providing and/repairing road infrastructure and road elements in Blackspot areas, such as providing/adding zebra crossing traffic signs, traffic lights, noise tape, improving road shoulders, and others.